Bird Banding - Saxena, V. S. (Indian Forester, 1971)
Bird Banding or Bird Ringing has assumed greater importance during the last two decades all over the World. Banding has dispelled many mistaken notions about birds. It has helped in the study of migration and migratory routes, life histories, longevity, breeding pattern, etc., of birds. In India, Dr. Salim Ali, of Bombay Natural History Society has taken up Bird Banding projects and, during the last about three years, over 70,000 birds have been ringed. In S.E. Asia, under schemes sponsored by MAPS (Migratory Animals Pathological Survey), 8,27,000 birds have been handed during the 5 years period 1964-68. The Bird Banding record in U S.A. is so numerous that they use electronic computers for processing the data. A lot remains to be done in our country.